Design of remotely, locally triggered shape-memory materials based on bicontinuous polylactide/epoxidized natural rubber thermoplastic vulcanizates via regulating the distribution of ferroferric oxide. (29th September 2019) - Huang, Jiarong; Fan, Jianfeng; Yin, Shiheng; Chen, Yukun
Abstract: In this work, we successfully designed remotely, locally thermal/magnetic/light triggered shape memory biobased polylactide/epoxidized natural rubber thermoplastic vulcanizates (PLA/ENR TPVs) via regulating the distribution of ferriferrous oxide (Fe3 O4 ). The TPVs exhibited novel bicontinuous structure, which played a vital role in shape memory effect (SME). The distribution of Fe3 O4 in the TPVs was regulated by changing the feeding sequence of Fe3 O4 during the dynamic vulcanization. Exhilaratingly, when Fe3 O4 was selectively distributed in the ENR phase, the biobased TPVs exhibited the highest R f ( 99%) and R r (>90%) even after five cycles because of the impeccable structure and reinforcement of ENR. Meanwhile, the TPVs also exhibited super-toughness (88.06 kJ/m 2 ) without sacrificing its tensile strength. Moreover, the incorporation of Fe3 O4 provided the TPVs with remotely/locally triggered SME, in which the TPVs could quickly recover to their initial shape in an alternating magnetic field or under near-infrared light (808 nm), which showed great potential in intelligent medical devices. Graphical abstract: Image 1